AN ANALYSIS OF THE DIFFERENTIATION STRATEGIES OF RURAL FOUNDRIES IN THE BEGINNING OF THE 20TH CENTURY IN THE PROVINCE OF QUEBEC - Lisa Baillargeon; Patrice Gélinas (Essays in Economic and Business History, 2009)
The business model and strategic position of Quebec's rural foundries at the beginning of the 20th century is virtually unknown. Inferences have been made based on pictorial and oral data sources. This data reveals that successful rural foundries were, in essence, confined to producing and selling agricultural tools to local farmers on an as-needed basis, because large urban foundries were already mass-producing domestic and industrial objects. In contrast, use of detailed accounting records and advertising publications of three rural foundries over the 1900 to 1914 period provides a clearer picture of the production and of the clientele of those rural foundries. Analysis of these sources suggests that the strategic business model of rural foundries was much more elaborate than the existing literature posits. Rural owner-managers of the early 20th century were sophisticated strategists, marketers, and operators.